Editorial – International Journal of Sustainable Energy Planning and Management Vol 14 - Østergaard, Poul Alberg (International Journal of Sustainable Energy Planning and Management, 2018)
This editorial introduces the 14th volume of the International Journal of Sustainable Energy Planning and Management, which addresses transition pathways for Sweden’s transportation sector, and for the West African power system towards low-carbon. Also, industrial symbiosis with the aim of providing district heating in Aalborg and prerequisites for energy transitions are addressed.